S168 Cortical unit and field activity during sleep cyclicity. Issue 9 (September 2017) - Ulbert, Istvan
Abstract : Objectives: The cortical slow oscillation emerging from the non-rapid eye movement sleep facilitates the long term consolidation of declarative memories, however our knowledge about its neural mechanisms in humans is rather limited. Methods: To elucidate the intracortical neuronal mechanisms of slow cortical activity in humans, laminar multichannel microelectrodes were chronically implanted into the cortex of patients with drug resistant focal epilepsy undergoing cortical mapping for seizure focus localization. In addition, similar measurements were taken from acute cortical slices of the patients under in vitro conditions. Results: Intracortical laminar local field potential gradient, multiple unit and single unit activities were recorded during slow wave sleep, related to simultaneous electrocorticography, and analyzed with current source density and spectral methods. We have found major supragranular contribution to the total cortical action potential and wide frequency band (10–200 Hz) synaptic/trans-membrane activity accompanied by spatially synchronized and relatively low firing rates. Similar results were obtained from the in vitro studies. Discussion: These findings provide evidence that slow cortical activity in humans is characterized by hyperpolarizing currents associated with suppressed firing, alternating with high oscillatory synaptic/trans-membrane activity with increased firing. Our results emphasize the major involvement of supragranular layers. Conclusions: The major supragranular activation in humans and the relatively low single firing rates, which has rather synchronous onset across layers are in contrast with results from animal models. Significance: Our results indicate that human slow cortical activity may use alternative neuronal mechanisms to accommodate to the demands of higher level cognitive and expanded memory functions.